Monitoring and Assessment of Land Use/Land Cover Changes in Elgezira-Aba Locality, White Nile State, Sudan using geospatial technology (University of Khartoum Journal of Agricultural Sciences, 2021)
Desertification as major environmental problem in Sudan seriously affected the livelihood and food security of population. Poor land use and climatic variability are the major causes of the desertification. This study focused on assessing and mapping of chanes land use and land cover (LU/LC) as drivers to desertification processes in the ElGezira-Aba Locality, White Nile State, Sudan. Two images (173/51) acquired by ETM+ and OLI/TIRS for years 2000 and 2016 were analyzed. Standard digital image processes were performed including layer stacking, supervised image classification, area calculation, accuracy assessment and post-classification change detection. In the years 2000 and 2016, respectively, forest covered 3838 Ha(15 %) and 1449 Ha (5.9 %), open forest covered 2749 Ha (11 %) and 1085 Ha (4.5%), grassland covered 2354 Ha (10 %) and 1315 Ha (5.4 %), rainfed mechanized agriculture covered 377 Ha (2 %) and 1914 Ha (8 %), irrigated scheme covered 2255 Ha (9 %) and 5051 Ha (20.8 %), fallow land covered 3791 Ha (5 %) and 1577 Ha (6 %), bareland covered 3938 Ha (16 %) and 1425 Ha (5.9 %), sand dunes covered 998 Ha (4 %) and 1165 Ha (4.8 %), water bodies covered 2219 Ha (9 %) and 3605 Ha (14 %) and urbanization covered 1794 Ha (7 %) and 5698 Ha (23 %). Overall classification accuracies for years 2000 and 2016, respectively were 86.39 % and 87.89 %, while overall kappa statistics were 0.8452 and 0.8594. Pronounced decrease in vegetation cover (forest, open forest and grassland) was recorded in favors of agriculture (irrigated scheme, rainfed mechanized agriculture)and urbanization. Sand dunes and Water bodies were increased. The dominant desertification processes were vegetation deterioration and wind erosion as a result of inappropriate agricultural activities, overgrazing and expansion of urban areas. The study concluded the necessity of protection natural resources by adoption of proper urban and land use planning in addition to use of geospatial technologies in monitoring of these resources.
Keywords: Desertification; Land Use/Land Cover; White Nile State; Sudan